How do Party organizations' boundary-spanning behaviors control worker unrest? A case study on a Chinese resource-based state-owned enterprise. Issue 2 (13th February 2017) - Lu, Jingfu; Li, Min
Abstract : Purpose: The purpose of this paper is to understand the boundary-spanning behaviors of Party organizations, and the processes and constraints of these behaviors in controlling worker unrest in Chinese resource-based state-owned enterprises in the "new work-unit system" using boundary-spanning theory. Design/methodology/approach: This case study was carried out in a resource-based state-owned enterprise in the "new work-unit system" in China. The research utilized interviews and archival documents, and then coded and analyzed the data using NVivo. Findings: In China, Party organizations' boundary-spanning behaviors (PBSBs) in labor relations management are identified, and classified into the behaviors of the ambassador, task coordinator, and scout. Worker unrest can be controlled by these behaviors through the mediation effect of the behaviors of agents in the "new work-unit system" but can also be provoked in the transformation of the "new work-unit system." Originality/value: The Communist Party plays a key role in labor relations management in China's SOEs; however, this role has not been explored in any depth. This study builds a model to reveal the "black box" in which the PBSBs influence the agents' behaviors and how the agents' behaviors then influence the workers, and in this way control worker unrest.